2000
DOI: 10.1017/s0031182099005594
|View full text |Cite
|
Sign up to set email alerts
|

Functional ryanodine receptor channels in flatworm muscle fibres

Abstract: Caffeine, which stimulates intracellular Ca2+ release channels known as ryanodine receptor (RyR) channels, induces contraction of individual muscle fibres dissociated from the trematode Schistosoma mansoni, and the turbellarians Dugesia tigrina and Procerodes littoralis. Caffeine is much more potent on S. mansoni fibres (EC50 0.7 mM) than those from D. tigrina or P. littoralis (3.2 mM and 4.6 mM, respectively). These caffeine-induced contractions are blocked by ryanodine, confirming the presence of functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 7 publications
2
13
0
Order By: Relevance
“…For example, under these same conditions in which extracellular Ca 2+ is taken away, caffeine can elicit contraction via a ryanodine-sensitive intracellular store [18]. Since YIRFamide does not elicit contractions under the same conditions, it demonstrates that the FLP contraction does not utilize this intracellular store, and reinforces the conclusion that the FLP-induced contractions depend on an influx of extracellular Ca 2+ (Figure 2).…”
Section: Resultssupporting
confidence: 62%
“…For example, under these same conditions in which extracellular Ca 2+ is taken away, caffeine can elicit contraction via a ryanodine-sensitive intracellular store [18]. Since YIRFamide does not elicit contractions under the same conditions, it demonstrates that the FLP contraction does not utilize this intracellular store, and reinforces the conclusion that the FLP-induced contractions depend on an influx of extracellular Ca 2+ (Figure 2).…”
Section: Resultssupporting
confidence: 62%
“…Furthermore, the addition of ryanodine induced the contraction of whole worms, in vitro. These data were corroborated by Day et al (2000) which have showed that caffeine, an agonist of RyR, was able to contract isolated muscle fibres. In this way we may propose that the presence of sarcoplasmic reticulum calcium stores, with both SERCA and RyR, is essencial to support worm contraction.…”
Section: Resultssupporting
confidence: 60%
“…Experimental observations also suggest the possibility for drug selectivity. For example, S. mansoni muscle fibres show RyR-like Ca 2+ responses that are activated by caffeine but insensitive to the classical RyR blockers, ruthenium red and neomycin [118]. Drugs with selectivity for insect RyRs have been described and these have been utilized to develop novel insecticides, which do not affect mammalian RyRs [119].…”
Section: Discussionmentioning
confidence: 99%